Strategi Penerapan Konsep Pemisahan Berbasis Seks Menurut Ibnu Sahnun Pada Pendidikan Tingkat Menengah Dalam Membentuk Karakter - Rahma, Farida Nur; Supraha, Wido; Hidayat, Tatang; Kusumah, Mada Wijaya (PT. Student Rihlah Indonesia, 2025)
The background of this study is the moral degradation of adolescents, especially due to promiscuity. This could lead Indonesia to a state of “promiscuity emergency.” This is due to the absence of a social system that regulates socializing or interaction between men and women, whether in the family, school, or community. Especially in schools, systems or rules that regulate interaction between men and women are only implemented in a small number of Islamic schools. The purpose of this research is to analyze the strategy of implementing the concept of sex-based separation according to Ibn Sahnun at the secondary education level. This research is categorized as library research with data obtained from books related to Ibn Sahnun's thoughts, particularly Adaab al Mu'allimin. The method used in this research is descriptive research based on its purpose, qualitative research based on its process, and basic research based on the expected research results. Through this research, four things related to the concept of gender-based separation according to Ibn Sahnun were found. First, Islam as a perfect religion has provided a system of life that is able to protect the intellect and honor of men and women. Second, history shows that throughout the ages, caliphs from any dynasty, especially those ruling in Africa, have applied the concept of gender-based segregation in their educational systems. Third, modern research, whether conducted by Islamic or non-Islamic schools, indicates that the application of the concept of gender segregation can enhance the quality of learning. Fourth, strategies for implementing the concept of gender-based segregation must be carried out systematically and integrally.